Problems and Prospects of the Youth of Modern Uzbekistan - Murodova Aziza Murod qizi (International Journal on Integrated Education, 2022)
In today's Uzbekistan, children and young people under 30 make up 60% of the population. In 15-20 years, they will become the largest workforce Uzbekistan has ever had, providing a unique opportunity to take the country to a new level of social and economic development. Developing a strategic long-term vision for youth capital formation based on evidence and the views of young people will help to leverage the available demographic dividend. In this article, the author reveals the opportunities and positive impact young people can have on the future, as well as the possible threats and challenges to social and national identity of uzbek youth.